PERSEPSI PESERTA DIDIK TENTANG MOTIVASI KERJA GURU BK DI KELAS XI SMAN 1 BASA AMPEK BALAI KECAMATAN BASA AMPEK BALAI TAPAN KABUPATEN PESISIR SELATAN - Desnita, Elia; Kasih, Fitria; Zaini, Ahmad (Bimbingan dan Konseling, 2014)
The background of this researchÂ is about participantsâ perception about work motivation of course and concelingteacher. In the field, it is foundedcourse and conceling teacher that is still least dicipline in doing main purpose. Alike: course and conceling teacher comes which is late at school and abcent while time work. Many course and conceling teachers only sit down at office when time work in order to service of course and conceling that do not walk with good. Course and conceling teacher can cause behaviour of participants which appear problems such as, get out from the class, fighting, disturb friends which is studied, not dicipline for the teacher and run away while teaching learning process. Focus of this research is about: 1. Work motivation of course and conceling teacher in giving service of course and conceling at school. 2. Work motivation of course and conceling teacher doing support activity service of course and conceling at school. This research is Qualitative Descriptive Reseach to describe real condition. Population of the research is all of participants class XI SMAN 1 Basa Ampek Balai tahun 2013/2014 that is amount 289 person. Sample of the research sums 72 person, take of sampling uses Simple Random Sampling. Tool of collecting the data uses questionares. The data analysis is used percentage formula. The result of the research expresses that: 1. Work motivation of teacher in giving service of course and conceling at school that is fit enough of 44,61%. 2. Work motivation of teacher to do supporting activity of course and conceling at school which is appropriate enough of 38,88%.